2016
DOI: 10.2113/gseegeosci.22.2.157
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Failure by Internal Erosion of Geosynthetic Clay Liners Used in Freshwater Reservoirs

Abstract: Geosynthetic clay liners (GCLs) are often used as lining materials for freshwater reservoirs. To irrigate agricultural land without depleting groundwater, surface water is stored in these artificial ponds. In this study, hydraulic conductivity tests were performed on GCLs placed in flexible-wall permeameters under hydraulic heads of up to 50 m in order to investigate the risk of internal erosion. In these tests, base pedestals made of Plexiglas with uniform circular voids were placed beneath the GCLs instead o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…After each hydraulic head increase, the hydraulic pressure acting on the GCL was kept constant for a period of 12 days. This period was chosen because a sudden increase in permittivity and then, the initiation of internal erosion for the tested GCLs was obtained in almost 12 days in previous studies [2,7,10]. Hydraulic head of 30 m was maintained by taking the cell pressure, influent pressure at the top of the GCL and effluent pressure at the bottom of the GCL as 550, 530 and 235.7 kPa respectively [19].…”
Section: Triaxial Permeability Testsmentioning
confidence: 99%
See 3 more Smart Citations
“…After each hydraulic head increase, the hydraulic pressure acting on the GCL was kept constant for a period of 12 days. This period was chosen because a sudden increase in permittivity and then, the initiation of internal erosion for the tested GCLs was obtained in almost 12 days in previous studies [2,7,10]. Hydraulic head of 30 m was maintained by taking the cell pressure, influent pressure at the top of the GCL and effluent pressure at the bottom of the GCL as 550, 530 and 235.7 kPa respectively [19].…”
Section: Triaxial Permeability Testsmentioning
confidence: 99%
“…This could be the main reason why the unconfined compressive strength of the GCLs increased due to an increase in the biopolymer content [17,24]. The results of some previous studies showed that internal erosion of the GCL was mainly related to the grain size of the subgrade soil beneath the GCL and the hydraulic load acting on the GCL [2,[5][6][7][8]. As the grain size and the hydraulic load increase, the internal erosion risk also increases.…”
Section: Unconfined Compression Testsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the GCLs have some advantages over the CCLs such as having lower hydraulic conductivity (<10 −10 m/s), lower thickness (4–10 mm), lower cost, less labor work and faster installation [ 72 , 77 , 78 ]. The most critical component of a GCL that determines the hydraulic performance of the barrier material is the bentonite layer [ 79 , 80 , 81 ]. A waste disposal area in Kütahya, Turkey before and after the placement of a barrier system that was composed of a geomembrane-laminated GCL is shown in Figure 4 .…”
Section: Solid Waste Disposal Facilities and Their Potential Role As A Source For Microplasticsmentioning
confidence: 99%